Effects of crustacean waste as feed on growth performances of siamese fighting fish (betta splendens) - Satya Narayana Rao Ramasamy; Assis Kamu; Connie Fay Komilus (Sarhad Journal of Agriculture, 2024)
The Siamese fighting fish (Betta splendens) are widely known as essential and demanded ornamental fish in Malaysia. This fish is attractive and elegant that it is being cultured domestically. Meanwhile, crustacean crab is produced about 40 % and it being discharged about 60 % to 80 % as biomass into the environment. As this waste contains protein that could enhance growth rate, it could be a good choice to be used as alternate source of feed for fighting fish. The objectives of this study are to determine proximate composition in formulated fish feed using crustacean waste and to examine effect of crab waste in fish feed on growth performances on Betta splendens. A total of 54 fishes with average weight (±0.035 g) was used for 20-days feeding trial using six treatments in triplicates namely TC (100% krill; 0% crab waste), T1 (80% krill; 20% crab waste), T2 (60% krill; 40% crab waste), T3 (40% krill; 60% crab waste), T4 (20% krill; 80% crab waste) and T5 (0% krill; 100% crab waste) respectively. Growth indices such as Body Weight Gain (BWG), Feed Conversion Ratio (FCR), Feed Intake (FI), and Survival Rate (SR) were observed every 10 days while water quality parameters like pH, dissolved oxygen, and temperature were taken every 4 days for monitoring purpose. It can be concluded that T1 (80 % krill 20 % crab waste) with high protein (30.02 %) and low lipid (5.43%) is best treatment that led to good FCR and BWG for small fish.